2006
DOI: 10.1369/jhc.5a6821.2005
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression and Localization of Insulin-like Growth Factors and Their Receptors throughout Amelogenesis in Rat Incisors

Abstract: (SO) S U M M A R Y Insulin-like growth factors (IGFs) are expressed in many tissues and control cell differentiation, proliferation, and apoptosis. In teeth, the temporo-spatial pattern of expression IGFs and their receptors has not been fully characterized. The purpose of this study was to obtain a comprehensive profile of their expression throughout the life cycle of ameloblasts, using the continuously erupting rat incisor model. Upper incisors of young male rats were fixed by perfusion, decalcified, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…This case is of special interest because it is the fi rst reported case of leprechaunism with these features, because most patients do not survive long enough to develop them. Yamamoto et al 22 found mRNA and protein signals for IGF-I and -II and their receptors in enamel organ of rat incisors throughout amelogenesis. Hence, there is a strong possibility that these molecules act as an autocrine/paracrine system that infl uences not only cell differentiation but also the physiological activity of ameloblasts.…”
Section: Discussionmentioning
confidence: 99%
“…This case is of special interest because it is the fi rst reported case of leprechaunism with these features, because most patients do not survive long enough to develop them. Yamamoto et al 22 found mRNA and protein signals for IGF-I and -II and their receptors in enamel organ of rat incisors throughout amelogenesis. Hence, there is a strong possibility that these molecules act as an autocrine/paracrine system that infl uences not only cell differentiation but also the physiological activity of ameloblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The expression pattern is similar to the localization of BMP4, FGF3, FGF9, and FGF10 in the developing incisor (Harada et al 1999(Harada et al , 2002Wang et al 2007). IGF and EGF also aVect ameloblast diVerentiation, and are localized in the incisor enamel formation region (Joseph et al 1999;Martineau-Doiz茅 et al 1991;Yamamoto et al 2006). Hsp25 is expressed in both ameloblasts and odontoblasts.…”
Section: Discussionmentioning
confidence: 63%
“…Among these factors, the insulin-like growth factors (IGFs) have been proposed as autocrine/paracrine regulators of in vivo tooth development (Caton et al 2005;Yamamoto et al 2006) and the molecular weight of IGF is less than 12.5 kDa. Therefore, IGFs are promising candidate soluble factors for mediation of the stimulation of ameloblastin mRNA and protein expression in HAT-7 cells.…”
Section: Discussionmentioning
confidence: 99%